Trends in emerging markets finance, institutions and money - Duc Khuong Nguyen; Stéphane Goutte (MDPI, 2020)
Since the waves of financial liberalization in the 1980s, emerging market economies have been accessible to foreign investors. Altogether, they contributed up to 43.8% of the global GDP in 2018, and many of them, such as China, India, Bangladesh, Philippines, Myanmar and Vietnam from 2010 to 2019, are among the fastest-growing economies in the world. Given the high economic growth, the assets issued by companies in emerging markets are viewed as a new set of investment opportunities for global investors and fund managers who seek to improve the risk-adjusted performance of their portfolios. In addition to their risky profile due to the lack of transparency as well as stable and matured institutions, their recent development path faces a number of challenges arising not only from the slow pace of economic reforms but also from their increased integration with the world. Geopolitical risks, the US-China trade wars, and rising policy uncertainty around the world are expected to reduce their growth potential and performance. This Special Issue dedicates special attention to the current dynamics of emerging financial markets, as well as their perspectives of development as a key driver for sustainable firms and economies. Accordingly, the focus is particularly placed on market integration and interdependence, valuations and risk management practices, and the financing means for inclusive growth.
Keywords: 330; Schwellenländer; Finanzmarktregulierung; Wirtschaftswachstum; Marktanteil; Wirtschaftsreform